A minimalist multifunctional nano-prodrug for drug resistance reverse and integration with PD-L1 mAb for enhanced immunotherapy of hepatocellular carcinoma - Ting Zou; Yun Huang; Zongtao Zhou; Shuangyan He; Jia Liu; Yalan Chen; Hongdu Liu; Zhonghui Luo; Miaoxin Liu; Hua Wei; CuiYun Yu (Journal of Nanobiotechnology)
Abstract Clinical treatment of hepatocellular carcinoma (HCC) with 5-fluorouracil (5-FU), the primary anticancer agent, remains unsatisfactory due to the glutathione (GSH)-associated drug resistance and immunosuppressive microenvironment of HCC. To develop a facile yet robust strategy to overcome 5-FU resistance for enhanced immunotherapy treatment of HCC via all dimensional GSH exhaustion, we report in this study construction of a minimalist prodrug consisting of 5-FU linked to an indoleamine-(2,3)-dioxygenase (IDO) inhibitor (IND) via a disulfide bridge, FU-SS-IND that can further self-assemble into stabilized nanoparticles, FU-SS-IND NPs. Specifically, besides the disulfide linker-induced GSH exhaustion, IND inhibits GSH biosynthesis and enhances the effector function of T cells for turning a “cold” tumor to a “hot” one, which synergistically achieving a tumor inhibition rate (TIR) of 92.5% in a 5-FU resistant mice model. Most importantly, FU-SS-IND NPs could upregulate programmed death ligand 1 (PD-L1) expression on the surface of tumor cells, which enables facile combination with immune checkpoint blockade (ICB) for a ultimate prolonged survival lifetime of 5-FU-resistant tumors-bearing mice. Overall, the minimalist bioreducible nano-prodrug developed herein demonstrates great translatable potential for efficiently reversing drug resistance and enhancing immunotherapy of HCC.